Digital Storytelling as a Tool for Language Learning in Young Learners: Insights from Literature - Ernadewi Kartikasari, S.Pd., M.Pd; Hendi Pratama; Seful Bahri (2025)
Integrating technology into language learning has become increasingly important in modern education. This library research explores the role of digital storytelling as a transformative teaching tool for teaching English to young learners. This study highlights how digital storytelling can be a fun and effective way to improve language skills, spark creativity, and help children develop critical thinking. It is grounded in constructivist learning theories focusing on active participation and meaningful learning experiences. The research method involved a comprehensive literature review, analysing various studies and scholarly articles demonstrating digital storytelling's effectiveness in educational settings. The analysis focused on the experiences and outcomes shared by educators and students in classrooms where digital storytelling was used. The findings show that digital storytelling powerfully captures young learners' attention and helps deepen their understanding of language concepts. Students demonstrated improved vocabulary, better storytelling skills, and greater motivation to engage with English. Additionally, the literature suggests that digital storytelling creates a more interactive and collaborative learning environment, allowing for personalized learning experiences. In conclusion, this library research highlights the importance of adopting innovative teaching approaches, such as digital storytelling, to prepare young learners for a globalized world where digital literacy is crucial. The results indicate that incorporating digital storytelling into English language teaching can lead to more effective and engaging learning experiences for young learners.